Efficacy of daclatasvir-based quadruple therapy in nonresponder patients infected by hepatitis C virus genotype 4: the ANRS HC32 QUATTRO study. Issue 3 (March 2018) - Roulot, Dominique; Thibault, Vincent; Laforest, Claire; Fontaine, Hélène; Bronowicki, Jean-Pierre; Asselah, Tarik; Bourlière, Marc; Canva, Valérie; Leroy, Vincent; Loustaud-Ratti, Véronique; Ouzan, Denis; Zoulim, Fabien; et al.
Abstract : Background: A few direct antiviral agents have been studied in difficult-to-treat patients infected by hepatitis C virus (HCV) genotype 4 (GT4). The efficacy of daclatasvir (DCV), asunaprevir (ASV), pegylated interferon and ribavirin (Peg-IFN/RBV) association was investigated in these patients. Patients and methods: This open-label, single-arm, phase 2 study was conducted in HCV GT4 patients who were null or partial responders to Peg-IFN/RBV. Patients received 24 weeks of DCV (60 mg, once daily), ASV (100 mg, twice daily) and Peg-IFN/RBV. The primary endpoint was sustained virologic response at post-treatment week 12 [sustained virologic response (SVR)12]. Results: Sixty patients were included; 45 (75%) were previous null responders and 27 (45%) had cirrhosis. The most frequent subtypes were GT4a (48%) and GT4d (27%) with 25% of the patients being infected with other subtypes such as 4c, 4r, 4f, 4k, 4j and 4q. The global SVR12 was 95% (90% confidence interval: 90.4–99.6) and 96.3% (90% confidence interval: 87.5–99.5) in cirrhotic patients. All patients achieving SVR12 also achieved SVR24. Previous Peg-IFN/RBV response, IL28b genotype, cirrhosis status or GT4 subtypes did not influence SVR12 rates. Serious adverse events occurred in 13% of the patients, four being cirrhotic and four noncirrhotic. Three (5%) patients stopped HCV therapy prematurely: one because of virologic breakthrough and two because of serious adverse events. Grade 3/4 laboratory abnormalities included leukopenia (33%), neutropenia (27%), thrombocytopenia (4%) and transaminases increase (2%). Conclusion: Association of DCV plus ASV and peg-IFN/RBV for 24 weeks demonstrated a high rate of SVR12 in HCV GT4-infected prior nonresponders, independently of the cirrhotic status or the GT4 subtype. The safety profile was acceptable, even in cirrhotic patients. Abstract : Supplemental Digital Content is available in the text.